Utilidad clínica del laboratorio Inmunológico - Carrasco, Patricia; Navarrete, Carmen; Afani, Alejandro (Revista Hospital Clínico Universidad de Chile, 1996)
CLINICAL UTILITY OF INMUNOLOGY LABORATORY.The clinical utility of the laboratory of inmunology in the diagnosis, evolution and prognosis of the different inmunological, reumathological and allergical diseases are analized.